Pengaruh Work Motivation dan Digital Culture terhadap Work Productivity melalui Work Engagement pada Karyawan PT. Pegadaian - Hidayah, Fitriana Nurochmatul; Wardoyo, Dewie Tri Wijayati (Universitas Negeri Surabaya, 2024)
This research aims to measure and analyze the influence of work motivation and digital culture on work productivity through work engagement. This research is causal research that uses a quantitative approach, with a population consisting of 64 employees and a sample of 55 employees. The data analysis in this research applies SEM-PLS with the contribution of SmartPLS 4.0 software. The results of this research prove that work motivation has a significant positive effect on work productivity, work motivation has a significant positive impact on work engagement, digital culture has a significant positive effect on work productivity, digital culture has a considerable positive impact on work engagement, work engagement has a significant positive effect on work productivity, work engagement mediates the relationship between work motivation and work productivity, and work engagement mediates the relationship between digital culture and work productivity. This research means that if a company wants to increase employee work productivity, the company must be able to provide positive energy as a form of work motivation and a good digital culture to increase employee work engagement.